2014
DOI: 10.3389/fncel.2014.00024
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes expressing mutant SOD1 and TDP43 trigger motoneuron death that is mediated via sodium channels and nitroxidative stress

Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal paralytic disorder caused by dysfunction and degeneration of motor neurons. Multiple disease-causing mutations, including in the genes for SOD1 and TDP-43, have been identified in ALS. Astrocytes expressing mutant SOD1 are strongly implicated in the pathogenesis of ALS: we have shown that media conditioned by astrocytes carrying mutant SOD1G93A contains toxic factor(s) that kill motoneurons by activating voltage-sensitive sodium (Nav) channels. In contrast, a rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
106
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(113 citation statements)
references
References 87 publications
7
106
0
Order By: Relevance
“…This suggests that at least some of the detrimental effects seen with C3aR inhibition could be due to the lack of C3a-mediated reduction of astrocytes and microglia in this mouse model of ALS. This supports many studies where they have shown non-neuronal neighbouring cells (astrocytes and microglia) release toxic factors that are detrimental to motor neuron survival (Julien, 2007, Henkel et al, 2009, Fritz et al, 2013, Rojas et al, 2014. Although we showed increased microglia mRNA levels (Entpd1) in hSOD1 G93A x C3aR -/-mice when compared to hSOD1 G93A mice at midsymptomatic stage, we also showed a decrease in monocyte mRNA level (Ly6C) in hSOD1 G93A x C3aR -/-mice at the same age.…”
Section: 35supporting
confidence: 91%
“…This suggests that at least some of the detrimental effects seen with C3aR inhibition could be due to the lack of C3a-mediated reduction of astrocytes and microglia in this mouse model of ALS. This supports many studies where they have shown non-neuronal neighbouring cells (astrocytes and microglia) release toxic factors that are detrimental to motor neuron survival (Julien, 2007, Henkel et al, 2009, Fritz et al, 2013, Rojas et al, 2014. Although we showed increased microglia mRNA levels (Entpd1) in hSOD1 G93A x C3aR -/-mice when compared to hSOD1 G93A mice at midsymptomatic stage, we also showed a decrease in monocyte mRNA level (Ly6C) in hSOD1 G93A x C3aR -/-mice at the same age.…”
Section: 35supporting
confidence: 91%
“…6,7 Muscle cramps occur in most patients with ALS during the course of the disease 13 and frequently cause distress. 14 Mexiletine, a cardiac antiarrhythmic agent and use-dependent sodium channel blocker, has recently been demonstrated to inhibit neuronal hyperexcitability and prevent cell death in a motor neuron cell line exposed to cultured media from astrocytes engineered to express the human SOD1 gene 15,16 and could potentially benefit patients with ALS.…”
mentioning
confidence: 99%
“…Thus, in transgenic hSOD1 G93A ALS mice, heightened excitability is evident before or shortly after birth [30][31][32]. Also, embryonic spinal cord cultures of 4-7 DIV have elevated persistent inward Na + currents when treated with astrocyte conditioned media from SOD1 G93A mice [33]; this study showed that astrocyte conditioned media from hSOD1 G93A mice target Na v 1.2 and Na v 1.3.…”
Section: Discussionmentioning
confidence: 53%
“…al. [33], conditioned media from astrocytes expressing mutant SOD1 selectively lead to motoneuron death through voltage-gated sodium channels. The authors of that study also indicated that incubation of the motoneuron cultures in mutant SOD1 and TDP 43 astrocyte conditioned medium with sodium channel blockers such as mexiletine (antiarrhythmic drug targeting Na v channel receptor site, [46], spermidine (a polyamine acting as an activity-dependent Na v channel blocker [47]) or a riluzole neural excitability suppressor via Na v channels [5,9]) inhibit both motoneuron death and nitro-oxidative stress.…”
Section: Discussionmentioning
confidence: 99%